Mining Together : Large-Scale Mining Meets Artisanal Mining, A Guide for Action - World Bank (Washington, DC, 2013)
The present guide mining together-when large-scale mining meets artisanal mining is an important step to better understanding the conflict dynamics and underlying issues between large-scale and small-scale mining. This guide for action not only points to some of the challenges that both parties need to deal with in order to build a more constructive relationship, but most importantly it sheds more light on some potential interventions for conflict prevention, management, and even transformation. This guide, then, represents a step in the right direction to start transforming the relationship between large-scale and artisanal miners through win-win solutions that emerge out of the genuine interaction and dialogue of all stakeholders involved: governments, companies, communities, miners and development organizations. Large-Scale Mining (LSM) companies increasingly come across Artisanal and Small-scale Mining (ASM) workers during their exploration or production activities in the developing world. The ASM-LSM relationship is often conflictual because both types of miners compete for the same resource or because they perceive each other as a threat. However the ASM-LSM relationship is now also undergoing a largely positive evolution in part thanks to new Corporate Social Responsibility (CSR) commitments. This guide is the result of this collaboration and provides an informative overview of the growing experiences of the most typical ASM-LSM issues and guidance for appropriate interventions.